27. KERJASAMA INDONESIA, MALAYSIA DAN SINGAPURA DI SELAT MALAKA DALAM MENANGANI PERAMPOKAN BERSENJATA TAHUN 2004-2013 - Avita Nariyanti Putri; Reni Windiani; Marten Hanura (Journal of International Relations Diponegoro, 2016)
Indonesia, Malaysia and Singapore formed cooperation to handle armed robbery in MalaccaStrait in 2004 named Malsindo. The type of this researchis analytic describtive usingqualitative method to apply neoliberalism theory. This research is aimed to know the reasonmeasures to combat armed robbery cases in Malacca Strait between 2004-2013. The result ofthis researchfinds that 11 September 2001 inUnited States had triggered fear among coastalstates about the potential attack to merchant ships in Malacca Strait, thus caused MalsindoCooperation had just formalized in 2004. This research also finds that measures taken by partsstates to combat armed robbery consists of Malacca Strait Sea Patrol (MSP) which waslaunched in 2004, Eyes in The Sky (EIS) which was launched in 2005 and MSP-IS in 2006.